Determinación del impacto del consumo de productos adelgazantes (parches, pastillas y té) en mujeres entre las edades de 18 a 40 años en la ciudad de Quito y diseño de una propuesta de consumo responsable. - Carrión Gutiérrez, Evelyn Noemí (2013)
In the present investigation will be revealed the level of consumption of slimming products such as tea, pills and patches, this occurs because many women today want to have a better figure, and so the influence of society has caused a strong impact on the minds of those who consume them. As the main objective of this research are: Determine the impact of consumption of slimming products (patches, lozenges and tea) in women aged 18-40 years in the city of Quito. Specific objectives of this research are:Deepen the mainstream on responsible consumption that exists in the market and in our country. Conduct an assessment of the consumption of slimming products.Develop a proposal for the responsible consumption of slimming products.